Factors Affecting Acceptance and Use of Moodle: An Empirical Study Based on TAM - Šumak, B.; Heričko, M.; Pušnik, M.; Polančič, G. (Informatica)
Factors Affecting Acceptance and Use of Moodle: An Empirical Study Based on TAM